Pathway mapping reveals antiretroviral treatments' targeted cell cycle regulation in lung cancer. (2020) - Marima, Rahaba; Hull, Rodney; Kandhavelu, Jeyalakshmi; Dlamini, Zodwa; Penny, Clement
Abstract: The human cell cycle is a tightly regulated process with checkpoints in place to ensure genomic integrity. Cyclin/cyclin dependent kinases (CDKs) complexes drive the progression of the cell cycle while CDK-inhibitors (CDKIs) halt the cell cycle. Deregulation of the cell cycle is a hallmark of lung cancer. TP53 and FOXO transcription factors share similar mechanisms in the regulation of the cell cycle. Lung carcinogenesis in the antiretroviral (ARV) era remains to be understood. This study aimed at mapping the biological pathways related to the human cell cycle that are influenced by the ARVs (Efavirenz-EFV and Lopinavir/ritonavir-LPV/r) treatment in A549 and MRC-5 lung cells. For this purpose, Reactome database was used to map these pathways. In addition, the Database for Annotation, Visualisation and Integrated Discovery (DAVID) was used for functional enrichment analysis in a set of genes and to visualise differentially expressed genes within a particular KEGG pathway, and also to perform Gene Ontology. Furthermore, the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) database was used to determine the protein-protein interaction of the differentially expressed gene (DEG) targets. Reactome analysis revealed a decrease in DNA replication and an increase in response to external stimuli and DNA repair genes in both normal and adenocarcinoma lung cancer models. A further increase in apoptotic genes is observed in the cancer cells in response to ARV treatment. Interestingly, the FOXO pathway was also shown to be upregulated in the test (ARV) groups. KEGG pathway shows a reduction in cyclin/CDK activity in ARV treated models. STRING analysis illustrates a direct and strong interaction between DNA damage and response (DDR) genes upregulated by ARV exposure. Analysis from all three databases suggests the cytotoxic and anti-proliferative effects of EFV and LPV/r on lung cancer.